Disaster Awareness, Preparedness, and Belief of Residents of Selected Barangays in Angeles City - Basilio, Matthew Andrei (MALATA SAINS INDONESIA, 2025)
Introduction: Disasters pose significant risks to communities, impacting safety, health, and preparedness. Angeles City frequently experiences natural hazards, necessitating an assessment of residents' disaster awareness, preparedness, and beliefs. Objectives: This study evaluates these aspects among residents in six selected barangays, identifying gaps and the role of disaster nursing in healthcare response and education. Methods: A cross-sectional descriptive design was utilized, selecting 396 respondents through cluster sampling. Communities were divided into streets, randomly chosen via the fishbowl method, with all households on selected streets included. A 91-item questionnaire integrating the Disaster Awareness and Preparedness Questionnaire and the General Disaster Preparedness Belief Scale was used for data collection. Researchers conducted house-to-house surveys, and data were analyzed using descriptive statistics and Pearson correlation through SPSS version 29. Results: Indicate moderate disaster awareness (x̄=3.49), with high awareness of typhoons, earthquakes, fires, and floods, but lower awareness of volcanic eruptions and landslides. Preparedness is generally high (x̄=4.22), with typhoons ranking highest and landslides lowest, though gaps remain in evacuation and safety practices. Disaster belief is notably high (x̄=3.80), with perceived benefits scoring highest and perceived barriers lowest. Pearson correlation analysis revealed significant positive relationships between awareness and preparedness (r=.37), awareness and belief (r=.25), and preparedness and belief (r=.38), all at p<.001. Conclusions: These findings underscore the interconnection of knowledge, action, and perception, and highlight the vital role of nurses in advancing disaster preparedness through education, early warning systems, training, and community engagement.